2019
DOI: 10.1007/jhep10(2019)114
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous symmetry breaking in fermionic random matrix model

Abstract: A fermionic random matrix model, which is a 0-dimensional version of the SYK model with replicas, is considered. The replica-off-diagonal correlation functions vanish at finite N , but we show that they do not vanish in the large N limit due to spontaneous symmetry breaking. We use the Bogoliubov quasi-averages approach to studying phase transitions. The consideration may be relevant to the study of the problem of existence of the spin glass phase in fermionic models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The holographic boundary dual of the JT gravity in spacetime with M boundaries is the M-replica SYK model in the low energy limit [65][66][67][68]. The studies of [61,[69][70][71][72][73] show that the nonperturbative completion of SYK involves nontrivial replica-nondiagonal saddle points. The replica-nondiagonal structures in SYK with replica interaction [73][74][75][76] demonstrate nontrivial phase structures and symmetry breaking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The holographic boundary dual of the JT gravity in spacetime with M boundaries is the M-replica SYK model in the low energy limit [65][66][67][68]. The studies of [61,[69][70][71][72][73] show that the nonperturbative completion of SYK involves nontrivial replica-nondiagonal saddle points. The replica-nondiagonal structures in SYK with replica interaction [73][74][75][76] demonstrate nontrivial phase structures and symmetry breaking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between the ensemble averaging and semiclassical nature of the large N expansion raises questions about its structure, in particular about the replica trick and the difference between quenched and annealed averaging [48][49][50][51]. The disorder averaging was shown to be of great benefit for studies of fine-grained quantum chaos in SYK [10,13,21,23,24,29,34], because it provides a mechanism to emphasize the universal RMT behavior which is built into the theory.…”
Section: Jhep03(2021)031mentioning
confidence: 99%
“…The more suitable quantity for probing the replica-nondiagonal structure is the Bogolyubov quasi-average [34,40]. In our case we define it as follows:…”
Section: Quasi-averagingmentioning
confidence: 99%
“…In particular, it was shown that the replica-nondiagonal saddle points of the replica field path integral are related to the ramp behavior of the spectral form-factor [14]. Replica-nondiagonal structures of saddle points of SYK-like models were also studied in [24,[29][30][31][32][33][34], in particular in relation to the issue of spin glasses and replica symmetry breaking. From the gravity point of view, the nonperturbative effects arising from the subleading saddle points are related to the topologies of higher genus [15,18,35], and they probe discrete spectrum of black hole microstates and are important for the recovery of lost information [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation